2010
DOI: 10.1053/j.gastro.2009.12.052
|View full text |Cite
|
Sign up to set email alerts
|

SAFETY Study: Alanine Aminotransferase Cutoff Values Are Set Too High for Reliable Detection of Pediatric Chronic Liver Disease

Abstract: Background & Aims The appropriate alanine aminotransferase (ALT) threshold value to use for diagnosis of chronic liver disease in children is unknown. We sought to develop sex-specific, biology-based, pediatric ALT thresholds. Methods The screening ALT for elevation in today’s youth (SAFETY) study collected observational data from acute care children’s hospitals, the national health and nutrition examination survey (NHANES, 1999–2006), overweight children with and without non-alcoholic fatty liver disease (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
403
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 411 publications
(419 citation statements)
references
References 26 publications
7
403
2
7
Order By: Relevance
“…In contrast, added sugar intake did not appear to be associated with elevated levels of ALT (surrogate for NAFLD) for the aggregate adolescent population. We used a cut-off value of 25 U/l, representing the 95th percentile of ALT for non-overweight adolescents of US NHANES (33) . We also used 40 U/l as the cut-off value for ALT and similar results were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, added sugar intake did not appear to be associated with elevated levels of ALT (surrogate for NAFLD) for the aggregate adolescent population. We used a cut-off value of 25 U/l, representing the 95th percentile of ALT for non-overweight adolescents of US NHANES (33) . We also used 40 U/l as the cut-off value for ALT and similar results were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The Screening ALT for Elevation in Today's Youth (SAFETY) study shows that conventional ALT cutoff values are set too high for the reliable detection of pediatric NAFLD. 24 In the National Health and Nutrition Examination Survey (NHANES) study, the 95th percentile levels for ALT in healthy weight, metabolically normal, liver disease-free patients were 25.8 U/L (boys) and 22.1 U/L (girls).…”
Section: Discussionmentioning
confidence: 99%
“…And the recommended ULN ALT was 30 U/L for men and 19 U/L for women respectively. 18,[22][23][24] Based on the previous results it is found that, recent ULN ALT greatly increase the number of asymptomatic patients with abnormal ALT values, and would identify more patients with nonalcoholic fatty liver disease (NAFLD) and clinically mild HBV/HCV infection.…”
Section: Introductionmentioning
confidence: 99%